(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2025)
The study examined the Village Savings and Loan Associations (VSLAs) on the livelihood of women groundnut farmers in Donga Local Government Area (LGA), Taraba State. The objectives were to examine the level of contribution participation in VSLAs had on the livelihood of women groundnut farmers, determine factors influencing women groundnut farmers’ participation in VSLA. Multistage random sampling technique was used in sampling a total of 84 participating women groundnut farmers in Village Savings and Loan Associations (VSLAs). Data were collected using a structured questionnaire and analyzed using descriptive statistics and regression analysis. Among respondents, 91.7% were active VSLA members, contributing varying amounts per cycle with a mean contribution of N38, 332.83 and interest of N34, 106.64 (representing 88.98% of the mean savings at the end of a circle). The result showed that 67.9% of the loan accessed from the pooled savings was used for farming purposes, while proceeds from the savings after a circle was used in supporting livelihood in the purchase of Christmas groceries, payment of children school fees and purchase of food items, ranking 1st, 2nd and 3rd, respectively. Regression analysis reveals significant predictors of VSLA membership to include age, education, farming experience, and income from groundnut farming at p < 0.01, and farm size at p<0.05. Constraints such as limited funds, inadequate training/capacity building and poor management of pooled funds were the leading challenges to women groundnut farmers participation in the association. It was concluded that VSLAs are a good source of funding for their farming activities and a good investment opportunity, the return of which contributed to their livelihood. The study recommended the need for targeted interventions to ensure access to funding, enhance financial literacy, promote participation in VSLAs and improve their agricultural production.